2022
DOI: 10.15587/1729-4061.2022.267161
|View full text |Cite
|
Sign up to set email alerts
|

Application of persimmon syrup to increase the biological value and organoleptic indicators of bread

Abstract: One of the factors hindering the widespread use of persimmon syrup in baking is the lack of knowledge of its functional properties for the production of a wide range of bread products due to its chemical composition. Based on this, a study of the method of obtaining persimmon syrup, quantitative changes in the nutritional content of the first-grade “Azamatli-95” wheat flour, persimmon syrup of the “Hyakume” variety, mixtures of wheat flour and persimmon syrup, bread with the addition of persimmon syrup was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Sulfur is an "anti-inflammatory" mineral, contributes to the destruction of microbes and parasites, improves immunity, helps maintain the oxygen balance necessary for the normal functioning of the brain, ensures normal regeneration of body cells, which is able to resist tissue destruction by free radicals and, therefore, promotes rejuvenation processes [17]. WHO recommendations amount to 13 mg/kg per 24 h in healthy adults, which for a 70 kg person equates to 910 mg/d.…”
Section: Discussion Of the Experimental Results Of The Research Of Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur is an "anti-inflammatory" mineral, contributes to the destruction of microbes and parasites, improves immunity, helps maintain the oxygen balance necessary for the normal functioning of the brain, ensures normal regeneration of body cells, which is able to resist tissue destruction by free radicals and, therefore, promotes rejuvenation processes [17]. WHO recommendations amount to 13 mg/kg per 24 h in healthy adults, which for a 70 kg person equates to 910 mg/d.…”
Section: Discussion Of the Experimental Results Of The Research Of Th...mentioning
confidence: 99%
“…The content and mineral composition of rose hips depends on the type and environmental conditions [16]. The benefits of nutrients, vitamins, and minerals for the human body are widely described in the work [17].…”
Section: Introductionmentioning
confidence: 99%
“…Functional nutrition, a concept studied in detail by Bayramov et al (2022), consists in eating foods that favourably affect the human body. It has been proved that this is the key to longevity, stress resistance, normal development and improving the quality of life of the population of the planet.…”
Section: Discussionmentioning
confidence: 99%
“…The research of Bakhshalieva et al (2023) proved that at an altitude of 600-800 m above sea level, the content of vitamin C and sugars in the fruit of Oriental persimmon is lower than in those varieties of Oriental persimmon plants that grow at an altitude of 200-300 m above sea level. Bayramov et al (2022) conducted a study on the benefits of nontraditional herbal supplements as iodine-containing foods. The nutritional and biological value of spices (ginger, turmeric, dried persimmon, and watercress seeds), amino acids, and the content of major minerals, especially iodine, were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Paper [5] reports the results of a study of the aromatic substances of persimmon, which are represented by tyrosine, tryptophan, phenylalanine, vanillin, as well as representatives of monomeric phenolic compounds confiryl, sinap, etc. It is shown that these substances have a calming effect on the nervous system, improve well-being and increase performance person.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%